A noble metal supported NH2-UIO-66-COF TFHB-BD Nanocomposite, method of preparation and use thereof
Patent Information
- Application Number
- CN202610673935.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-15
- Publication Date
- 2026-10-13
AI Technical Summary
然而,该技术仍存在以下不足:(1)金纳米颗粒被COF层部分覆盖,导电增强作用未充分发挥,且易堵塞MOF孔道;(2)材料表面缺乏氨基等活性官能团,不利于适配体高效固定;(3)应用场景与适配体传感器需求不匹配:该复合材料是针对光电化学传感器和蛋白靶标检测而设计,未针对啶虫脒等小分子农药的电化学适配体传感器进行功能优化
1.本发明采用化学还原法将贵金属纳米颗粒负载于MOF-COF复合材料的最外层表面,避免了贵金属纳米颗粒对MOF孔道的堵塞,使其充分暴露于材料表面。对本发明实施例1制备的纳米复合材料进行表征观察,结果显示:大量球形凸起均匀分散在NH2-UIO-66-COFTFHB-BD复合材料表面,证明该纳米复合材料具有高负载量和稳定的结构。电化学测试结果进一步表明,本发明制备的贵金属负载型NH2-UIO-66-COFTFHB-BD纳米复合材料显著扩大了电极传感界面的表面积,增加了电活性位点的数量。
Smart Images

Figure CN122895504A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodetection technology, specifically relating to a noble metal-loaded NH2-UIO-66-COF TFHB-BD Nanocomposites, preparation methods and applications. Background Technology
[0002] Accurate detection of acetamiprid pesticide residues in Chinese medicinal herbs and food is of great significance for ensuring pesticide safety and public health. However, existing detection methods suffer from problems such as complex operation, reliance on expensive instruments, or insufficient sensitivity. Therefore, there is a need to develop a simple, rapid, reliable, and accurate acetamiprid detection strategy.
[0003] Electrochemical biosensors, with their advantages of high sensitivity, rapid response, low cost, and easy miniaturization, have broad application prospects in pesticide residue detection. DNA aptamers, as excellent recognition elements, have been widely used in the construction of electrochemical aptamer sensors. To further improve the detection performance of trace acetamiprid, nucleic acid amplifiers have been gradually integrated into the sensing system. However, biosensors based on DNA hairpin dimers mediated by dual catalytic circuits still have limitations such as the lack of integration of high-performance functional materials, making it difficult to meet the accurate detection needs of practical samples such as traditional Chinese medicine.
[0004] The selection of functional materials is crucial for improving sensor performance. Metal-organic frameworks (MOFs) possess excellent electrochemical properties, high conductivity, high specific surface area, and high active sites, but pure MOFs lack stability. Covalent organic frameworks (COFs), on the other hand, have large pore sizes, high stability, and abundant conjugated systems. Combining COFs with MOFs can achieve complementary advantages, synergistically enhancing the conductivity, stability, and aptamer loading capacity of the materials to improve detection sensitivity.
[0005] Existing research has attempted to use MOF and COF composites for sensing applications. For example, patent application CN115598342A discloses a Ti-MOF@DM-LZU1@Au composite material, in which gold nanoparticles are loaded into the interfacial pores of MOF and COF. However, this technology still has the following shortcomings: (1) the gold nanoparticles are partially covered by the COF layer, the conductivity enhancement effect is not fully utilized, and it is easy to block the MOF pores; (2) the material surface lacks active functional groups such as amino groups, which is not conducive to the efficient fixation of aptamers; (3) the application scenarios do not match the requirements of aptamer sensors: this composite material is designed for photoelectrochemical sensors and protein target detection, and has not been functionally optimized for electrochemical aptamer sensors for small molecule pesticides such as acetamiprid. The detection of small molecule pesticides requires higher conductivity of the sensing interface, aptamer loading, and signal conversion efficiency. This material has not been specifically optimized for the needs of small molecule trace detection in terms of conductivity, functional group design, and pore structure, making it difficult to directly meet the high-sensitivity detection requirements of acetamiprid residues in traditional Chinese medicine. Summary of the Invention
[0006] To address the technical problems existing in the background art, the present invention provides a noble metal-supported NH2-UIO-66-COF TFHB-BD Nanocomposite materials, preparation methods and applications, including NH2-UIO-66-COF TFHB-BD Nanocomposite materials have the characteristics of excellent conductivity, large specific surface area, high active sites, high aptamer loading and structural stability, and are widely used in the field of electrochemical biosensors, especially suitable for highly sensitive detection of pesticide residues such as acetamiprid in Chinese medicinal materials.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A noble metal-supported NH2-UIO-66-COF TFHB-BD The nanocomposite material comprises a metal-organic framework (MOF), a covalent organic framework (COF), and noble metal nanoparticles. The covalent organic framework is grown on the surface of the metal-organic framework to form a composite material (MOF-COF), and the noble metal nanoparticles are loaded on the composite material. The metal-organic framework is an amino-functionalized zirconium-based metal-organic framework.
[0008] Further specified, the covalent organic framework is grown on the surface of the metal-organic framework by in-situ growth method, wherein the covalent organic framework is formed by the condensation polymerization of organic ligands under acetic acid catalysis, wherein the organic ligands are 1,3,5-trialdehyde phloroglucinol (TFHB) and benzidine (BD), and the molar ratio of the metal-organic framework to the covalent organic framework is 0.5:1-4:1.
[0009] Further specifying, the mass ratio of the noble metal nanoparticles to the composite material is 0.2:1, and the noble metal nanoparticles are gold, silver, or platinum nanoparticles.
[0010] A noble metal-supported NH2-UIO-66-COF TFHB-BD The preparation method of nanocomposite materials includes the following steps: Step 1: The metal-organic framework NH2-UIO-66 was obtained by reacting zirconium source and amino-functionalized organic ligand under acetic acid regulation using a hydrothermal method. Step 2: Take the NH2-UIO-66 from Step 1, add the organic ligands 1,3,5-trialdehyde phloroglucinol (TFHB) and benzidine (BD) to form a covalent organic framework through condensation polymerization. The covalent organic framework is grown in situ and covalently crosslinked on the surface of the metal-organic framework to form a composite material. Step 3: Mix the composite material obtained in Step 2 with a solution of noble metal nanoparticles to load the noble metal nanoparticles onto the surface of the composite material, thereby obtaining a nanocomposite material.
[0011] Further specifying, the zirconium source in step 1 is zirconium tetrachloride, and the amino-containing dicarboxylic acid ligand is 2-aminoterephthalic acid; the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is 1:1.
[0012] Further specified, the noble metal nanoparticle solution in step 3 is formed by reduction of a noble metal salt, wherein the noble metal salt is tetrachloroauric acid; the mass-volume ratio of the composite material to the noble metal nanoparticle solution in step 3 is 2 mg:3 mL.
[0013] Further specifying, the specific process of step 1 is as follows: Zirconium tetrachloride and 2-aminoterephthalic acid are simultaneously dissolved in dimethylformamide at a molar ratio of 1:1, acetic acid solution is added as a regulator, and the mixture is obtained by sonication for 12-18 min. The mixture is then transferred to a polytetrafluoroethylene lining and heated, washed, and dried for 8-14 h to obtain the metal-organic framework NH2-UIO-66.
[0014] Further specifying step 2, the steps are as follows: Prepare a mixed solution of o-dichlorobenzene and n-butanol at a volume ratio of 19:1; mix the metal-organic framework from step 1 with the mixed solution at a mass-volume ratio of 10-12 mg:1 mL; dissolve by sonication for 8-12 min; add acetic acid solution, then add the organic ligands 1,3,5-trialdehyde-resorcinol and benzidine; dissolve by sonication for 25-35 min; after dissolution, allow to stand at 20-30℃, centrifuge, wash three times, and dry at 55-65℃ for 8-12 h to obtain the composite material.
[0015] Further specifying step 3, it is as follows: heating the tetrachloroauric acid solution to boiling in an oil bath, adding sodium citrate solution at a volume ratio of 10:1, heating and stirring the solution until it turns wine red, stopping the heating, cooling to room temperature, and obtaining a gold nanoparticle solution; dissolving the composite material obtained in step 2 in the gold nanoparticle solution, stirring and washing three times, drying at 55-65 ℃ for 9-11 h, to obtain the nanocomposite material.
[0016] A noble metal-supported NH2-UIO-66-COF TFHB-BD Application of nanocomposite materials in the electrochemical detection of acetamiprid.
[0017] The beneficial effects of this invention are: 1. This invention employs a chemical reduction method to load noble metal nanoparticles onto the outermost surface of a MOF-COF composite material, avoiding the blockage of MOF pores by the noble metal nanoparticles and ensuring their full exposure on the material surface. Characterization and observation of the nanocomposite material prepared in Example 1 of this invention showed that a large number of spherical protrusions were uniformly dispersed in NH2-UIO-66-COF. TFHB-BD The surface of the composite material demonstrates that the nanocomposite exhibits high loading and a stable structure. Electrochemical testing further confirms that the noble metal-supported NH2-UIO-66-COF prepared in this invention... TFHB-BD Nanocomposite materials significantly increase the surface area of the electrode sensing interface and increase the number of electroactive sites.
[0018] 2. This invention uses NH2-UIO-66 as the MOF substrate, whose abundant amino functional groups provide ideal nucleation sites for the in-situ growth of COF. This nanocomposite material retains the high activity sites and large specific surface area of MOF, while leveraging the structural characteristics of COF to control the size and pore structure of the composite material, thereby increasing the aptamer loading to improve detection sensitivity and enhancing the bonding strength of the MOF-COF composite. Experiments show that both aptamer loading and immobilization stability are significantly improved.
[0019] 3. Addressing the high requirements for conductivity, aptamer loading, and signal conversion efficiency in the detection of small molecules such as acetamiprid, this invention achieves specialized optimization of material properties through noble metal surface exposure, introduction of amino functional groups, and hierarchical pore structure design. Electrochemical response and optimization experiments of the biosensor demonstrate that the biosensor constructed using the nanocomposite material of this invention exhibits significantly improved detection sensitivity, meeting the detection requirements for trace pesticide residues in complex samples such as traditional Chinese medicine. This nanocomposite material possesses high specific surface area, excellent conductivity, good biocompatibility, and high aptamer loading capacity, making it suitable for constructing electrochemical aptamer sensors for various targets (such as pesticides, toxins, and antibiotics). Furthermore, this invention allows for precise control of the reaction conditions for MOF synthesis, in-situ COF growth, and chemical reduction of noble metal nanoparticles, making it suitable for large-scale production. Attached Figure Description
[0020] Figure 1 This is a characterization result diagram of the nanocomposite material of Example 1 of the present invention, wherein (A) is COF TFHB-BD Fourier transform infrared spectra of TFHB and BD, (B) is Au@NH2-UIO-66-COF TFHB-BD NH2-UIO-66-COF TFHB-BD COF TFHB-BD Fourier transform infrared spectra of NH2-UIO-66, (C) is Au@NH2-UIO-66-COF TFHB-BD NH2-UIO-66-COF TFHB-BD COF TFHB-BD X-ray diffraction pattern of NH2-UIO-66, (D) is Au@NH2-UIO-66-COF TFHB-BD NH2-UIO-66-COF TFHB-BD X-ray photoelectron spectroscopy, (E) is a high-resolution X-ray photoelectron spectrum of Au 4f, and (F) is the spectrum of NH2-UIO-66 and NH2-UIO-66-COF. TFHB-BD N2 adsorption-desorption isotherm spectrum; Figure 2 Example 1NH2-UIO-66-COF of the present invention TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD The morphological images are shown, where (A) is a scanning electron microscope image of NH2-UIO-66, and (B) is a COF image. TFHB-BD Scanning electron microscope image, (C) is NH2-UIO-66-COF TFHB-BD Scanning electron microscope image (5µM), (D) is Au@NH2-UIO-66-COF TFHB-BD Scanning electron microscope image (500 nm); Figure 3 The above are electrochemical characterization diagrams of the nanocomposite materials prepared in Example 1 of this invention, where (A) is the cyclic voltammetry (CV) curve of the stepwise modified electrode, (B) is the electrochemical impedance spectroscopy (EIS) response diagram of the stepwise modified electrode, and (C) is the bare glassy carbon electrode (bare GCE) and NH2-UIO-66-COF. TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD CV comparison diagram; (D) is the CV curve of NH2-UIO-66 at 5 mM [Fe(CN)6] -3 / -4 The CV curves at scan rates of 10 mV / s–300 mV / s, where (E) represents the peak current (Ip, μA) of the NH₂-UIO-66 oxidation process as a function of the square root of the scan rate (ν). 1 / 2 The linear relationship between (F) and (UIO-66-COF) is shown in the graph. TFHB-BD At 5 mM [Fe(CN)6] -3 / -4 CV curves at scan rates of 10 mV / s-300 mV / s, where (G) represents NH2-UIO-66-COF. TFHB-BD Oxidation peak current (Ip, μA) versus the square root of scan rate (ν) 1 / 2 A linear relationship graph between Au@NH2-UIO-66-COF, where (H) represents Au@NH2-UIO-66-COF. TFHB-BD At 5 mM [Fe(CN)6] -3 / -4 CV curves at scan rates of 10 mV / s-300 mV / s, (I) is Au@NH2-UIO-66-COF TFHB-BD Oxidation peak current (Ip, μA) versus the square root of scan rate (ν) 1 / 2 A linear relationship diagram between ( ) and ( ); Figure 4 The COF prepared in Example 1 of this invention TFHB-BD Chemical structure diagram; Figure 5 The Au@NH2-UIO-66-COF nanocomposite material prepared in Example 1 of this invention TFHB-BD The high-resolution X-ray diffraction patterns are shown, where (A) is the C 1s level of carbon, (B) is the Zr 3d level of zirconium, (C) is the O 1s level of oxygen, and (D) is the N 1s level of nitrogen. Figure 6The images shown are scanning electron microscope (SEM) images of MOF and COF with different molar ratios in this invention. (A) is an SEM image (1µM) with a MOF:COF molar ratio of 0.5:1, (B) is an SEM image (3µM) with a MOF:COF molar ratio of 1:1, (C) is an SEM image (3µM) with a MOF:COF molar ratio of 2:1, (D) is an SEM image (5µM) with a MOF:COF molar ratio of 2:1, (E) is an SEM image (5µM) with a MOF:COF molar ratio of 3:1, and (F) is an SEM image (4µM) with a MOF:COF molar ratio of 4:1. Figure 7 NH2-UIO-66-COF prepared in Example 1 of this invention TFHB-BD The SEM mapping diagram, where Figure (A) is NH2-UIO-66-COF TFHB-BD Overall SEM image (10µM), (B) represents NH2-UIO-66-COF TFHB-BD SEM overall image (2µM), (C) is the surface distribution map of C element (2µM), (D) is the surface distribution map of O element (2µM), (E) is the surface distribution map of Zr element (2µM), and (F) is the surface distribution map of N element (2µM). Figure 8 This is a characterization diagram of the bare GCE composite material in this invention, where (A) represents the data within 5 mM [Fe(CN)6] at scan rates ranging from 10 mV / s to 300 mV / s. -3 / -4 The CV curve in the figure, (B) represents the peak anode current (Ip) versus the square root of the scan rate (ν). 1 / 2 The relationship curve between (). Detailed Implementation
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this disclosure. Rather, they are merely examples of methods consistent with some aspects of the invention as detailed in the appended claims.
[0023] The terminology used in this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The singular forms “a,” “the,” and “the” used in this invention and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any and all possible combinations of one or more of the associated listed items.
[0024] In the description of this application, it should be understood that the numerical labels before the steps do not indicate the order of the steps, but are only used to facilitate the description of this application and to distinguish each step, and therefore should not be construed as a limitation of this application.
[0025] This invention provides a noble metal-supported NH2-UIO-66-COF TFHB-BD The preparation method of nanocomposite materials includes the following steps: Step 1: The metal-organic framework NH2-UIO-66 was obtained by reacting zirconium source and amino-functionalized organic ligand under acetic acid regulation using a hydrothermal method. Step 2: Take NH2-UIO-66, add organic ligands 1,3,5-trialdehyde phloroglucinol (TFHB) and benzidine (BD) to form a covalent organic framework through condensation. The covalent organic framework is grown in situ and covalently crosslinked on the surface of the metal-organic framework to form a composite material. Step 3: Mix the composite material obtained in Step 2 with a solution of noble metal nanoparticles to load the noble metal nanoparticles onto the surface of the composite material, thereby obtaining a nanocomposite material.
[0026] Preferably, the zirconium source in step 1 is zirconium tetrachloride, and the amino-containing dicarboxylic acid ligand is 2-aminoterephthalic acid; the molar ratio of the metal-organic framework to the organic ligand TFHB.BD in step 2 is 1.4:1; the noble metal nanoparticle solution in step 3 is formed by reduction with a noble metal salt, wherein the noble metal salt is tetrachloroauric acid; and the mass-volume ratio of the composite material to the noble metal nanoparticle solution in step 3 is 2 mg:3 mL.
[0027] Preferably, the specific process of step 1 is as follows: zirconium tetrachloride and 2-aminoterephthalic acid are simultaneously dissolved in dimethylformamide at a molar ratio of 1:1, acetic acid solution is added as a regulator, and the mixture is obtained by sonication for 12-18 min. The mixture is then transferred to a polytetrafluoroethylene lining and heated, washed, and dried for 8-14 h to obtain the metal-organic framework NH2-UIO-66.
[0028] Preferably, step 2 specifically involves: preparing a mixed solution of o-dichlorobenzene and n-butanol at a volume ratio of 19:1; mixing the metal-organic framework from step 1 with the mixed solution at a mass-volume ratio of 10-12 mg:1 mL; dissolving by sonication for 8-12 min; adding acetic acid solution, then adding the organic ligands 1,3,5-trialdehyde-resorcinol and benzidine; dissolving by sonication for 25-35 min; centrifuging after standing at 20-30°C; washing three times; and drying at 55-65°C for 8-12 h to obtain the composite material.
[0029] Preferably, step 3 specifically involves: heating the tetrachloroauric acid solution to boiling in an oil bath, adding sodium citrate solution at a volume ratio of 10:1, heating and stirring the solution until it turns wine red, stopping the heating, and cooling to room temperature to obtain a gold nanoparticle solution; dissolving the composite material obtained in step 2 in the gold nanoparticle solution, stirring and washing three times, and drying at 55-65℃ for 9-11 h to obtain the nanocomposite material.
[0030] The present invention will be further described below with reference to embodiments.
[0031] Example 1 The noble metal-loaded NH2-UIO-66-COF provided in this embodiment TFHB-BD The preparation method of nanocomposite materials includes the following steps: Step 1: A hydrothermal method was used to synthesize the metal-organic framework. Specifically, 1 mmol of ZrCl4 and 1 mmol of 2-aminoterephthalic acid were simultaneously dissolved in 30 mL of dimethylformamide (DMF), and 5 mL of acetic acid was added as a modifier. After sonication for 15 min, the resulting mixture was transferred to a 100 mL polytetrafluoroethylene liner and heated at 120 °C for 24 hours. After the reaction was completed, the resulting NH2-UIO-66 powder was centrifuged and washed three times with DMF and anhydrous ethanol, and dried overnight at 60 °C to obtain the metal-organic framework NH2-UIO-66. Step 2: Synthesis of the composite material MOF-COF: Take 22 mg of the NH2-UIO-66 synthesized in Step 1, dissolve it in 2 mL of a mixed solution of o-dichlorobenzene (ODCD) and n-butanol (n-BUOH) with a volume ratio of 19:1, sonicate for 10 min, add 0.2 mL of acetic acid solution, and then add COF. TFHB-BD 11 mg of the organic ligand 1,3,5-trialdehyde phloroglucinol and 10 mg of benzidine were sonicated for 30 min until dissolved, and reacted at 25 °C for 72 h. After centrifugation, the mixture was washed three times each with tetrahydrofuran (THF), N,N-dimethylformamide (DMF), and methanol (MeOH), and dried at 60 °C for 10 h to obtain the composite material NH2-UIO-66-COF. TFHB-BD(MOF-COF); Step 3: Synthesis of Nanocomposite Materials: A 3.41% HAuCl4 solution was diluted to 100 mL with water. The solution was heated to boiling in an oil bath with stirring. 10 mL of sodium citrate solution was quickly added to the boiling solution, and the mixture was heated and stirred continuously for 15 min. The solution color changed from colorless to grayish-black, then to deep purple, and finally gradually to wine red. Heating was stopped, and stirring was continued until the solution cooled to room temperature. The resulting gold nanoparticle solution was collected and placed in a light-proof brown bottle, stored in a refrigerator at 4°C for later use. 2 mg of the synthesized MOF-COF was dissolved in 3 mL of the synthesized gold nanoparticle solution. The solution was magnetically stirred for 8 h, washed three times with ultrapure water, and dried at 60°C for 10 h to obtain Au@NH2-UIO-66-COF. TFHB-BD .
[0032] Example 2 This embodiment refers to the preparation method of Example 1, except that in step 3, tetrachloroauric acid is replaced with silver nitrate.
[0033] Example 3 This embodiment refers to the preparation method of Example 1, except that in step 3, tetrachloroauric acid is replaced with chloroplatinic acid.
[0034] Example 4 The noble metal-loaded NH2-UIO-66-COF provided in this embodiment TFHB-BD Application of nanocomposite materials in the preparation of electrochemical biosensors for detecting acetamiprid.
[0035] The fabrication method of the electrochemical aptamer sensor is as follows: Step 1: Prepare a solution of the nanocomposite material Au@NH2-UIO-66-COFTFHB-BD with a concentration of 1.5 mg / mL; Step 2: Grind the bare glassy carbon electrode with aluminum oxide powder, and then sonicate the ground bare glassy carbon electrode in ethanol and deionized water for 20 min. Step 3: Modify the bare glassy carbon electrode: Drop the Au@NH2-UIO-66-COFTFHB-BD solution prepared in step 1 onto the surface of the bare glassy carbon electrode after the pretreatment in step 2, and dry it to obtain the modified bare glassy carbon electrode Au@NH2-UIO-66-COFTFHB-BD / GCE; Step 4: Fixing and Sealing the Capture Hairpins: Take 10 μL of 2.5 μM capture hairpin H3 and anneal it: place it at 95 °C for 5 min, then cool it to 22-28 °C for 60 min to form a stem-ring hairpin structure. Add 3 μL of 1 mM solution containing tris(2-carboxyethyl)phosphine hydrochloride (TCEP) to stabilize the conformation of the H3 monomer hairpin. Drop it onto the electrode surface and incubate for 8 h to obtain H3 / Au@NH2-UIO-66-COFTFHB-BD / GCE. Drop 5 μL of 1 mM 6-mercapto-1-hexanol (MCH) blocking agent onto the surface of H3 / Au@NH2-UIO-66-COFTFHB-BD / GCE and incubate for 15 min to obtain MCH / H3 / Au@NH2-UIO-66-COFTFHB-BD / GCE. Step 5: Self-assembly: The first hairpin probe H1 and the second hairpin probe H2 are annealed in the same way as the annealing process for capturing hairpin H3 in Step 4 above, except that TCEP is not included, and 10 μL of the first hairpin structure dimer dH1 and 10 μL of the second hairpin structure dimer dH2 after annealing are obtained respectively. 10 μL of 1 μM DNA aptamer Apt, 20 μL of annealed first hairpin dimer dH1, second hairpin dimer and dH2 were introduced and self-assembled for 80 min to obtain dH2 / MCH / H3 / Au@NH2-UIO-66-COFTFHB-BD / GCE.
[0036] To further investigate the noble metal-loaded NH2-UIO-66-COF in the above embodiments TFHB-BD The performance of the nanocomposite material was tested to demonstrate the technical effectiveness of the present invention. The following tests were conducted.
[0037] Test 1: Structural Characterization of Nanocomposite Materials This test selected Au@NH2-UIO-66-COF prepared in Example 1. TFHB-BD Nanocomposite materials, raw materials TFHB and BD, and intermediate products NH2-UIO-66 and COF obtained in each step. TFHB-BD NH2-UIO-66-COF TFHB-BD Au@NH2-UIO-66-COF TFHB-BD It was characterized by Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) analysis, respectively.
[0038] Characterization results as follows Figure 1 As shown, Figure 1 (A) is COF TFHB-BDTFHB and BD infrared spectroscopy characterization, COF TFHB-BD The raw material BD is located at 3320 cm -1 and 3388 cm -1 The characteristic stretching vibration peak of the amino (-NH2) group at 1690 cm⁻¹ and the peak at 1690 cm⁻¹ in TFHB -1 The C=O stretching vibration peak of the aldehyde group at COF TFHB-BD They completely disappeared in the infrared spectrum. In COF TFHB-BD In the spectrum, 1617cm -1 A new absorption peak belonging to the imine bond appeared at [location], accompanied by a [value] cm⁻¹. -1 Vibrational peaks of the nearby benzene ring skeleton.
[0039] The above results indicate that the characteristic peaks of the raw material disappeared, and COF... TFHB-BD The presence of new C=N bond and aromatic ring CH bond characteristic peaks indicates the formation of imine bonds and the construction of a conjugated skeleton, thus proving that this COF... TFHB-BD Material synthesis successful, COF TFHB-BD Chemical structure such as Figure 4 As shown.
[0040] To further prove Au@NH2-UIO-66-COF TFHB-BD The nanocomposite material Au@NH2-UIO-66-COF was successfully prepared. TFHB-BD NH2-UIO-66-COF TFHB-BD COF TFHB-BD NH2-UIO-66 was characterized by infrared spectroscopy, as follows: Figure 1 As shown in (B), with NH2-UIO-66 and COF TFHB-BD Compared to the infrared spectrum, NH2-UIO-66-COF TFHB-BD With Au@NH2-UIO-66-COF TFHB-BD The nanocomposite materials all have values of 1569, 655, and 478 cm⁻¹. -1 The presence of a characteristic absorption peak at this point indicates that it corresponds to the skeletal vibration of the benzene ring and the stretching vibration of the Zr-O bond in NH2-UIO-66. (COF) TFHB-BD Contains a characteristic imine group formed by the condensation of an aldehyde and an amino group, in Au@NH2-UIO-66-COF TFHB-BD Typical infrared characteristic peak (1617 cm⁻¹) corresponding to C=N stretching vibration in nanocomposites -1 ).
[0041] The results showed that the skeletal integrity of NH2-UIO-66 was well maintained during the synthesis of the composite material, and the COF TFHB-BDBoth components, NH2-UIO-66 and Au@NH2-UIO-66-COF, are present. TFHB-BD In nanocomposite materials.
[0042] Powder X-ray diffraction was used to analyze Au@NH2-UIO-66-COF TFHB-BD Au@NH2-UIO-66-COF nanocomposite TFHB-BD NH2-UIO-66-COF TFHB-BD COF TFHB-BD The results of characterizing the NH2-UIO-66 crystal structure are as follows: Figure 1 As shown in (C), the characteristic diffraction peaks of pure NH2-UIO-66 are in high agreement with the standard simulated spectrum, indicating its high crystallinity; COF TFHB-BD The characteristic diffraction peaks are mainly concentrated in the range of 10°–30°; NH2-UIO-66-COF TFHB-BD The composite material retained the characteristic diffraction peaks of both components without peak shift, indicating that the COF grew in situ on the MOF surface without disrupting the crystalline phase of NH2-UIO-66, thus forming a crystalline hybrid structure. After loading gold nanoparticles (AuNPs), the X-ray diffraction pattern of the composite material showed no significant change, indicating that the introduction of AuNPs did not disrupt the NH2-UIO-66-COF. TFHB-BD Crystal phase structure of composite materials.
[0043] X-ray photoelectron spectroscopy was used to investigate the elemental composition of the nanocomposite material before and after loading gold nanoparticles, namely NH2-UIO-66-COF. TFHB-BD With Au@NH2-UIO-66-COF TFHB-BD The changes. Figure 1 X-ray photoelectron spectroscopy of D showed that NH2-UIO-66-COF TFHB-BD With Au@NH2-UIO-66-COF TFHB-BD All contained C, O, and Zr elements, confirming the successful construction of the MOF-COF framework. Au 4f signal was detected only in the latter, indicating that Au was successfully introduced.
[0044] Further analysis of Au@NH2-UIO-66-COF TFHB-BD A high-resolution XPS scan was performed, and the results are as follows: Figure 5 and Figure 1 As shown in E. Figure 5(A), (B), (C), and (D) show the fine spectra of C 1s, Zr 3d, O 1s, and N 1s, respectively: the characteristic peak of the C 1s spectrum is located at 284.8 eV, confirming the presence of the benzene ring skeleton and oxygen-containing functional groups; the characteristic peaks detected in the Zr 3d spectrum are located at 182.5 eV and 184.9 eV; the characteristic peak detected in the O 1s spectrum is located at 531.8 eV; and the characteristic peak detected in the N 1s spectrum is located at 399.5 eV, proving the successful formation of Schiff base bonds in COF.
[0045] like Figure 1 (E) Only Au@NH2-UIO-66-COF TFHB-BD XPS signals of Au4f were detected in the nanocomposite material, with two characteristic peaks located at 87.4 eV (Au4f5 / 2) and 83.5 eV (Au4f7 / 2), respectively; indicating that AuNPs have been successfully introduced into Au@NH2-UIO-66-COF. TFHB-BD In composite materials.
[0046] The above XPS results confirm Au@NH2-UIO-66-COF TFHB-BD Chemical structure of nanocomposites. To further investigate their pore structure characteristics, the chemical structures of NH₂-UIO-66 and NH₂-UIO-66-COF were tested at 77 K. TFHB-BD N2 adsorption-desorption isotherms of composite materials, such as Figure 1 As shown in (F), all samples were degassed at 100℃ for 12 h before testing. Both samples exhibited typical Type I isotherms with a small amount of Type IV characteristics, indicating that the materials are predominantly microporous, with a small amount of mesopores formed by particle aggregation. Calculated using the Brunauer-Emmett-Teller (BET) method, NH2-UIO-66 and NH2-UIO-66-COF... TFHB-BD The specific surface area of the composite material is 736 m². 2 g -1 and 224 m 2 g -1 . NH2-UIO-66, NH2-UIO-66-COF TFHB-BD The specific surface area of the composite material decreased significantly. This phenomenon can be attributed to the formation of a COF layer on the surface of NH2-UIO-66, which partially blocked the pores of the original MOF matrix and reduced the accessible specific surface area. However, the overall N2 adsorption-desorption isotherm indicates that the main microporous framework of NH2-UIO-66 remained intact, and the COF... TFHB-BDThe loading only partially filled the micropores and did not alter the intrinsic pore structure of the material, thus having no significant adverse effect on the detection of trace analytes. In summary, the above characterization results collectively confirm the target product NH2-UIO-66-COF. TFHB-BD The composite material was successfully prepared.
[0047] The microstructure and morphology of the prepared material were observed using electron microscopy to further verify Au@NH2-UIO-66-COF. TFHB-BD The nanocomposite material was successfully synthesized. First, scanning electron microscopy was used to analyze NH2-UIO-66-COF... TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD The morphology is characterized. For example... Figure 2 As shown in (A), NH2-UIO-66 exhibits an octahedral morphology; while COF TFHB-BD It has a rod-like structure, such as Figure 2 (B). NH2-UIO-66-COF TFHB-BD The composite material exhibits a hybrid morphology, with rod-shaped COF TFHB-BD Grown on the surface of NH2-UIO-66, such as Figure 2 (C). By adjusting the precursor molar ratio, for example... Figure 6 As shown, the optimal molar ratio was determined to be 2:1. Furthermore, elemental mapping analysis was performed as follows: Figure 7 This indicates that Zr and N elements are uniformly distributed in the composite material; while C and O elements are concentrated in the rod-shaped structural region, confirming the COF... TFHB-BD Successful growth was achieved on the NH2-UIO-66 surface. For Au@NH2-UIO-66-COF... TFHB-BD Numerous spherical protrusions can be observed to be uniformly dispersed in NH2-UIO-66-COF. TFHB-BD Nanocomposite surface such as Figure 2 (D). According to the above characterization results, Au@NH2-UIO-66-COF TFHB-BD The synthesis of nanocomposite materials has been successful.
[0048] Test 2 To verify the electrochemical performance of the nanocomposite material prepared in this invention, the nanocomposite material prepared in Example 1 was subjected to CV and EIS at 5 mM [Fe(CN)6]. -3 / -4 Characterization was performed in a solution with a pH of 7.4, and the results are as follows: Figure 3 As shown.
[0049] like Figure 3 (A) Cyclic voltammetry (CV) curves of the stepwise modified electrode and (B) Electrochemical impedance spectroscopy (EIS) response plots of the stepwise modified electrode are shown, where a is bare GCE and b is COF. TFHB-BDc is NH2-UIO-66, and d is NH2-UIO-66-COF. TFHB-BD It can be observed that the glassy carbon bare electrode (bare GCE) has a pair of reversible redox peaks and a semicircle (curve a); when NH2-UIO-66-COF is added to the electrode... TFHB-BD The study found a significant enhancement in the CV signal and a decrease in the EIS impedance (curve d), demonstrating the excellent conductivity of MOF and the strong stability of COF; while the addition of COF... TFHB-BD When combined with NH2-UIO-66 material, it was found that the peak current of the individual material decreased, but the EIS impedance increased (curves b, c), indicating that the conductivity of the individual material was poor, which hindered the transfer of electrons at the interface.
[0050] Further comparison of bare glassy carbon electrode (bare GCE) and NH2-UIO-66-COF TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD The CV comparison chart is as follows Figure 3 As shown in C, where a is bare GCE and b is NH2-UIO-66-COF TFHB-BD c is Au@NH2-UIO-66-COF TFHB-BD The results showed that, compared with bare GCE, NH2-UIO-66-COF TFHB-BD The peak current of the modified electrode was significantly enhanced; after further loading with gold nanoparticles, Au@NH2-UIO-66-COF TFHB-BD The peak current of the modified electrode reached its maximum, indicating that the introduction of gold nanoparticles significantly improved the conductivity and electrochemical activity of the composite material.
[0051] Further analysis of NH2-UIO-66 and NH2-UIO-66-COF TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD Different scan rates (10-300 mV / s) were performed at 5.0 mM [Fe(CN)6]. -3 / -4 CV analysis and electroactive area analysis. For example... Figure 3 D, 3F, and 3H respectively demonstrate NH2-UIO-66 and NH2-UIO-66-COF. TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD CV curves were obtained at scan rates ranging from 10 to 300 mV / s. The redox peak current gradually increased with increasing scan rate. (NH₂-UIO-66, NH₂-UIO-66-COF) TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD The collected oxidation peak current (Ip, μA) and the square root of the scan rate (ν) 1 / 2A linear relationship was established between them, as follows: Figure 3 E, 3G, and 3I show that the peak anodic current (Ip) of all three materials is related to the square root of the scan rate (ν). 1 / 2 The relationship between NH₂-UIO-66-COF and other parameters is good, indicating that the electrode reaction is diffusion-controlled. Calculations show that NH₂-UIO-66-COF... TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD The electroactive surface areas of the modified electrodes were 6.4 mm² and 6.6 mm², respectively. Further CV analysis and electroactive area analysis were performed on the bare GCE. Figure 8 A represents a scan rate in the range of 10 mV / s to 300 mV / s within 5 mM [Fe(CN)6]. -3 / -4 CV curve in Figure 8 B represents the peak anode current (Ip) and the square root of the scan rate (ν). 1 / 2 The relationship curve between NH2-UIO-66-COF is shown. The electroactive surface area of the bare GCE is 5.5 mm². TFHB-BD and Au@NH2-UIO-66-COF TFHB-BD The electroactive surface area of the modified electrodes was larger than that of the bare GCE electrodes, demonstrating that the composite material effectively increased the surface area of the electrode sensing interface and the number of electroactive sites. These results further confirm the efficacy of Au@NH2-UIO-66-COF. TFHB-BD The potential applications of composite materials in the field of biosensing and detection.
[0052] In summary, the noble metal-supported NH2-UIO-66-COF provided by this invention... TFHB-BD The nanocomposite material exhibits excellent conductivity, a large specific surface area, and a high number of active sites, resulting in not only high aptamer loading but also good structural stability. Electrochemical detection of acetamiprid using this material demonstrates high sensitivity and good selectivity for the residue. This fully demonstrates that the nanocomposite material is suitable for detecting acetamiprid in complex real-world samples and shows great potential in the field of electrochemical biosensing detection of pesticide residues.
Claims
1. A noble metal-supported NH2-UIO-66-COF TFHB-BD Nanocomposite materials, characterized in that, The nanocomposite material includes a metal-organic framework, a covalent organic framework, and noble metal nanoparticles. The covalent organic framework is grown on the surface of the metal-organic framework to form the composite material, and the noble metal nanoparticles are loaded on the composite material. The metal-organic framework is an amino-functionalized zirconium-based metal-organic framework.
2. The noble metal-supported NH2-UIO-66-COF according to claim 1 TFHB-BD Nanocomposite materials, characterized in that, The covalent organic framework is grown on the surface of the metal-organic framework by in-situ growth. The covalent organic framework is formed by the condensation polymerization of organic ligands under acetic acid catalysis. The organic ligands are 1,3,5-trialdehyde phloroglucinol and benzidine. The molar ratio of the metal-organic framework to the covalent organic framework is 0.5:1-4:
1.
3. The noble metal-supported NH2-UIO-66-COF according to claim 2 TFHB-BD Nanocomposite materials, characterized in that, The mass ratio of the noble metal nanoparticles to the composite material is 0.2:1, and the noble metal nanoparticles are gold, silver, or platinum nanoparticles.
4. A noble metal-supported NH2-UIO-66-COF TFHB-BD A method for preparing nanocomposite materials, used to prepare the noble metal-supported NH2-UIO-66-COF as described in any one of claims 1-3. TFHB-BD Nanocomposite materials, characterized in that, Includes the following steps: Step 1: The metal-organic framework NH2-UIO-66 was obtained by reacting zirconium source and amino-functionalized organic ligand under acetic acid regulation using a hydrothermal method. Step 2: Take the NH2-UIO-66 from Step 1, add the organic ligand 1,3,5-trialdehyde phloroglucinol and benzidine to form a covalent organic framework through condensation polymerization. The covalent organic framework is grown in situ and covalently crosslinked on the surface of the metal-organic framework to form a composite material. Step 3: Mix the composite material obtained in Step 2 with a solution of noble metal nanoparticles to load the noble metal nanoparticles onto the surface of the composite material, thereby obtaining a nanocomposite material.
5. The noble metal-supported NH2-UIO-66-COF according to claim 4 TFHB-BD A method for preparing nanocomposite materials, characterized in that, The zirconium source in step 1 is zirconium tetrachloride, the amino-containing dicarboxylic acid ligand is 2-aminoterephthalic acid, and the molar ratio of zirconium tetrachloride to 2-aminoterephthalic acid is 1:
1.
6. The noble metal-supported NH2-UIO-66-COF according to claim 4 TFHB-BD A method for preparing nanocomposite materials, characterized in that, The noble metal nanoparticle solution in step 3 is formed by reduction of a noble metal salt, wherein the noble metal salt is tetrachloroauric acid; the mass-volume ratio of the composite material to the noble metal nanoparticle solution in step 3 is 2 mg: 3 mL.
7. The noble metal-supported NH2-UIO-66-COF according to claim 5 TFHB-BD A method for preparing nanocomposite materials, characterized in that, The specific process of step 1 is as follows: Zirconium tetrachloride and 2-aminoterephthalic acid are simultaneously dissolved in dimethylformamide, acetic acid solution is added as a regulator, and the mixture is obtained by sonication for 12-18 min. The mixture is then transferred to a polytetrafluoroethylene lining and heated, washed, and dried for 8-14 h to obtain the metal-organic framework NH2-UIO-66.
8. The noble metal-supported NH2-UIO-66-COF according to claim 6 TFHB-BD A method for preparing nanocomposite materials, characterized in that, Step 2 is as follows: Prepare a mixed solution of o-dichlorobenzene and n-butanol at a volume ratio of 19:
1. Take the metal-organic framework from step 1 and mix it with the mixed solution at a mass-volume ratio of 10-12 mg:1 mL. Dissolve by sonication for 8-12 min. After dissolution, add acetic acid solution and add organic ligands 1,3,5-trialdehyde-resorcinol and benzidine at a molar ratio of 1.4:
1. Dissolve by sonication for 25-35 min. After dissolution, let stand at 20-30 °C, centrifuge, wash three times, and dry at 55-65 °C for 8-12 h to obtain the composite material.
9. The noble metal-supported NH2-UIO-66-COF according to claim 7 TFHB-BD A method for preparing nanocomposite materials, characterized in that, Step 3 is as follows: Heat the tetrachloroauric acid solution to boiling in an oil bath, add sodium citrate solution at a volume ratio of 10:1, heat and stir the solution until it turns wine red, then stop heating and cool to room temperature to obtain a gold nanoparticle solution; dissolve the composite material obtained in step 2 in the gold nanoparticle solution, stir and wash three times, and dry at 55-65 ℃ for 9-11 h to obtain the nanocomposite material.
10. The noble metal-supported NH2-UIO-66-COF according to any one of claims 1-3 TFHB-BD Nanocomposite materials or NH2-UIO-66-COF supported on noble metals according to any one of claims 4-9 TFHB-BD NH2-UIO-66-COF prepared by a method for preparing nanocomposite materials TFHB-BD Application of nanocomposite materials in the electrochemical detection of acetamiprid.
Citation Information
Patent Citations
Novel photoelectrochemical sensor, preparation method and CysC detection method
CN115598342A